Effective classroom management as determinants of students' achievement in economics in public secondary schools in Ibadan, Oyo state (2012)
The paper examined how teacher self-efficacy and teacher effective classroom management determined both interactively and individually students' achievement in secondary economics in Ibadan metropolis of Oyo state, Nigeria. Three hypotheses were tested at 0.05 level of significance. Multi-stage sampling technique was used to select six out of eleven local government area councils in Ibadan, 60 schools and subsequently 60 SS economics teachers as subject in study while their classes were used intact. Two instruments and students' classroom examination records in economics were used in collecting the data for the exercise. Findings were that while teacher self-efficacy and teacher classroom management effectiveness individually significantly determined the academic achievement of the students in economics when combined. It was, therefore, concluded that the latter might be as a result of the inability of the teachers to combine the two variables effectively or they were ill-motivated so they did not possess the capacity to effectively do so. It was recommended that teachers should be encoruaged to imbibe the spirit self-efficacy in carrying their assignments and be trained on how to effectively manage classroom effectively as well as efficiently.